A Systems View of the Heparan Sulfate Interactome. (February 2021) - Gómez Toledo, Alejandro; Sorrentino, James T.; Sandoval, Daniel R.; Malmström, Johan; Lewis, Nathan E.; Esko, Jeffrey D.
Heparan sulfate proteoglycans consist of a small family of proteins decorated with one or more covalently attached heparan sulfate glycosaminoglycan chains. These chains have intricate structural patterns based on the position of sulfate groups and uronic acid epimers, which dictate their ability to engage a large repertoire of heparan sulfate–binding proteins, including extracellular matrix proteins, growth factors and morphogens, cytokines and chemokines, apolipoproteins and lipases, adhesion and growth factor receptors, and components of the complement and coagulation system. This review highlights recent progress in the characterization of the so-called "heparan sulfate interactome, " with a major focus on systems-wide strategies as a tool for discovery and characterization of this subproteome. In addition, we compiled all heparan sulfate–binding proteins reported in the literature to date and grouped them into a few major functional classes by applying a networking approach.